"How to use it more?" Self-efficacy and its sources in the use of social media for knowledge sharing. Issue 1 (28th August 2019) - Alshahrani, Hussain; Rasmussen Pennington, Diane
Abstract : Purpose: The purpose of this paper is to investigate sources of self-efficacy for researchers and the sources' impact on the researchers' use of social media for knowledge sharing. It is a continuation of a larger study (Alshahrani and Rasmussen Pennington, 2018 ). Design/methodology/approach: The authors distributed an online questionnaire to researchers at the University of Strathclyde ( n =144) and analysed the responses using descriptive statistics. Findings: Participants relied on personal mastery experience, vicarious experience, verbal persuasion and emotional arousal for social media use. These elements of self-efficacy mostly led them to use it effectively, with a few exceptions. Research limitations/implications: The convenience sample utilised for this study, which included academic staff, researchers and PhD students at one university, is small and may not be entirely representative of the larger population. Practical implications: This study contributes to the existing literature on social media and knowledge sharing. It can help researchers understand how they can develop their self-efficacy and its sources in order to enhance their online professional presence. Additionally, academic institutions can use these results to inform how they can best encourage and support their researchers in improving their professional social media use. Originality/value: Researchers do rely on their self-efficacy and its sources to use social media for knowledge sharing. These results can help researchers and their institutions eliminate barriers and improve online engagement with colleagues, students, the public and other relevant research stakeholders.